2018
DOI: 10.1088/1757-899x/342/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility characteristics of Sabak Bernam Marine Clay

Abstract: It is important to carry out this study since this type of marine clay covers large coastal area of west coast Malaysia. This type of marine clay was found on the main road connecting Klang to Perak and the road keeps experiencing undulation and uneven settlement which jeopardise the safety of the road users. The soil is indicated in the Generalised Soil Map of Peninsular Malaysia as a CLAY with alluvial soil on recent marine and riverine alluvium. Based on the British Standard Soil Classification and Plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…This paper serves as a comparison between studied marine clay and several types of marine clay samples taken from various South East Asian locations [1]- [10], [12], [13], [16], [17], [20], [21], [24]- [35], [37]- [39], [42]. Significant variations of the geotechnical parameters have been found for the same region, even if not of the same borehole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper serves as a comparison between studied marine clay and several types of marine clay samples taken from various South East Asian locations [1]- [10], [12], [13], [16], [17], [20], [21], [24]- [35], [37]- [39], [42]. Significant variations of the geotechnical parameters have been found for the same region, even if not of the same borehole.…”
Section: Discussionmentioning
confidence: 99%
“…Some results have displayed odd values compared to the general tendencies seen for Arkine of Japan [2]- [4], Ashikari (Japan) [35], Oita Prefecture (Malaysia) [2], and Klang (Malaysia) [24]. Nevertheless, the value of liquid limit w LL is found to be not less than 60% [3], [30], [35]; whereas the plastic limit w PL is below 30% [9], [10], [17], [20], [21], [32], [34], [37]. Similarly, the natural water content wn is within the range of liquid limit if not higher [4], [5], [7], [10], [12], [16], [17], [20], [30], [32], [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compression index or recompression index can be found by performing an oedometer test in a laboratory. Diana et al [15] have used soft clay, a type of marine clay, to study the characteristics of the soft clay in terms of compressibility through a 1-D consolidation test. The results of the study found that the compression index value was 0.614 and the recompression ratio value was 0.169.…”
Section: Introductionmentioning
confidence: 99%